Climate Vulnerability in Solar Microgeneration: Analysis of the Impacts of Urban Flooding on Photovoltaic Systems - Diogo Antonio Queiroz Gomes; Filipe Cardoso Brito; Aloísio Santos Nascimento Filho; Eduardo Manuel de Freitas Jorge; Márcio Luis Valença Araújo; Natalia Silva Coimbra de Sá; Hugo Saba (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
The increased frequency of extreme weather events, especially floods, has exposed the vulnerability of photovoltaic microgeneration systems in urban areas. This theoretical, descriptive study analyzed the physical and operational impacts associated with flooding, focusing on three recurring categories in the literature: inverter damage, photovoltaic module failure, and electric shock risk. In addition to financial losses, structural damage was identified, which impacts the safety and resilience of these systems. The results highlighted the importance of preventive measures, such as elevating sensitive components, adopting moisture-resistant materials, and adopting safe shutdown protocols. The conclusion is that, although solar microgeneration is strategic for the energy transition, it directly depends on the adoption of adaptive solutions to mitigate vulnerabilities during extreme hydrometeorological episodes.